The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1103/physrevb.57.r9377
|View full text |Cite
|
Sign up to set email alerts
|

Charge ordering and disordering transitions inPr1xCaxMnO

Abstract: The magnetic-field dependence of optical spectra and their anisotropy have been investigated for a single crystal of Pr 1Ϫx Ca x MnO 3 ͑xϭ0.4͒ at 30 K. The charge-ordered ͑CO͒ state is transformed into a ferromagnetic metallic state by a magnetic field of 6.5 T, which is manifested in a huge change of optical spectra over a wide photon-energy region ͑0.05 eV-3 eV͒. The observed change in magnitude and anisotropy of the optical spectra with the external magnetic field has been elucidated in terms of the spin-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
58
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(64 citation statements)
references
References 18 publications
6
58
0
Order By: Relevance
“…The T variation of the absorption coefficient of this material is negligible at the center of the laserwavelength used in the photoexcitation. [19] We found that E THz tends to decrease as T is increased around 120 K. For further increase with T , E THz monotonically increases up to 230 K. Even at the room T , the THz radiation is clearly observed. These critical points matches with previously reported values; T CA , T N , and T CO/OO .…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…The T variation of the absorption coefficient of this material is negligible at the center of the laserwavelength used in the photoexcitation. [19] We found that E THz tends to decrease as T is increased around 120 K. For further increase with T , E THz monotonically increases up to 230 K. Even at the room T , the THz radiation is clearly observed. These critical points matches with previously reported values; T CA , T N , and T CO/OO .…”
mentioning
confidence: 74%
“…The energy of the optical pulse exceeds the charge-gap energy ∼0.5 eV of PCMO and nearly corresponds to the charge transfer energy from O 2p to Mn 3d band. [19] The pump-pulses chopped mechanically at 2 kHz were focused into the region of 30 µm in diameter by an object lens on the gap of the bow-tie antenna. In order to enhance the collection efficiency of the THz-pulse, we attached an MgO hemispherical lens on the backside of the MgO substrate.…”
mentioning
confidence: 99%
“…Another explanation is that the charge gap is affected by the electron-electron interaction. Such a correlationdriven enhancement of the gap is though to be present in several manganites like Bi 1−x Ca x MnO 3 (x = 0.74−0.82) [14], Pr 0.6 Ca 0 .4MnO 3 [15] and La 1−x Ca x MnO 3 (x ≥ 0.6) and in the nickelate NdNiO 3 [16] where the gap parameter is ∼ 20, ∼ 9, ∼ 10 and ∼ 20, respectively. The temperature dependence of the gap in all of the above cited 3d compounds fairly follows the BCS functional form while in BaVS 3 the transition appears in ∆ ch in a much sharper manner.…”
mentioning
confidence: 99%
“…In LCMO/BFO, the induced AFM order at the interface will increase θ ij in LCMO [Fig 3(a)], suppressing in-plane electron hopping. This results in a discernible difference between LCMO and LCMO/BFO in a high B field, which increases the alignment of the induced AFM spins [38,39] while keeping the ordered FM spins saturated. We note that neutron diffraction measurements on LSMO/BFO superlattices grown in the same system at LANL have revealed a reduced magnetization in the LSMO layers, supporting this hypothesis [48].…”
mentioning
confidence: 99%
“…The applied field enhances the spin alignment, increasing the conductivity, which reduces the polaronic peak and recovers the Drude-like feature [i.e., following the blue solid line from the lower to the upper panel in Fig. 1(b)] [25,[36][37][38][39][40][41].…”
mentioning
confidence: 99%